2019
DOI: 10.14254/2071-789x.2019/12-3/5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of innovativeness and innovation behavior on tourism SMEs performance: The case of Albania

Abstract: Though SMEs play a crucial role in countries' economic development, some of them succeed and others fail during their life cycle. In this regard, managers/owners continually have to identify the most significant factors that influence performance management. In addition, this is crucial for developing countries such as Albania, wherein such studies are lacking, furthermore, tourism sector is experiencing very fast development. Therefore, the purpose of this study is to empirically investigate the interplay of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 70 publications
4
37
0
Order By: Relevance
“…The individual results demonstrated that brand loyalty positively influenced brand image. These findings are consistent with previous studies, such as work by Tellefsen & Thomas (2005) and Domi et al (2019). The study further demonstrated that CSR has a positive and significant impact on brand image.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The individual results demonstrated that brand loyalty positively influenced brand image. These findings are consistent with previous studies, such as work by Tellefsen & Thomas (2005) and Domi et al (2019). The study further demonstrated that CSR has a positive and significant impact on brand image.…”
Section: Discussionsupporting
confidence: 93%
“…A few studies have demonstrated contradictory results, i.e. a significant influence of promotion on brand loyalty(Domi et al, 2019;Medzhybovska & Lew, 2019). A possible reason for these dissimilarities is the use of different approaches regarding cause promotion and brand loyalty.…”
mentioning
confidence: 99%
“…While innovativeness does not affect SMEs performance directly, its indirect effects through the mediation role of innovation behavior are significant. The results indicate that the more tourism sphere SMEs innovate in terms of ICT, cooperation (associations, networks), the more their performance will positively increase (Domi et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 94%
“…This technique has a very high response rate, roughly 95% (see e.g., Thornberry, 1987;Domi et al, 2019). Due to the time and costs associated with this method, we selected randomly 210 people.…”
Section: Methodsmentioning
confidence: 99%